The Influence of TikTok Social Media Use on Improving the Understanding of Fiqh in the Thaharah Chapter of Grade VII Students of MTs Al-Ihsan Kalijaring Jombang - Yusnita, Pingkan Rosi; Aisa, Aufia; Wardani, Dian Kusuma (Darul Yasin Al Sys, 2026)
Although digital media in Islamic religious education has received considerable scholarly attention, limited studies have specifically examined the use of TikTok social media to improve junior secondary students’ understanding of the thaharah chapter in fiqh. This study aims to examine the effect of TikTok content use on improving students’ understanding of thaharah and to describe students’ responses to its use as a learning medium. A quantitative experimental approach was employed, involving 50 Grade VII students of MTs Al-Ihsan Kalijaring Jombang selected through total sampling. Data were collected through pre-tests, post-tests, and a Likert-scale student response questionnaire. The instruments were tested for validity using Pearson product-moment correlation and for reliability using Cronbach’s Alpha. Because the data were not normally distributed, as indicated by the Shapiro–Wilk test (p < 0.05), hypothesis testing was conducted using the Wilcoxon signed-ranks test. The findings show that TikTok use significantly improved students’ understanding, with the mean score increasing from 41.00 in the pre-test to 76.80 in the post-test, representing an increase of 35.80 points or 87.32%. The Wilcoxon test produced an Asymp. Sig. (2-tailed) value of 0.000 < 0.05, while the N-Gain score reached 0.60, indicating a moderate level of improvement. The study concludes that TikTok is effective as an alternative learning medium for thaharah material. These findings contribute to Islamic education by demonstrating the potential of audiovisual social media content to support students’ conceptual understanding and provide practical implications for teachers in developing innovative digital learning media aligned with Generation Z’s learning characteristics. Future research may extend this study through longitudinal designs and broader samples.